ECG from basics to essentials : step by step - Stroobandt, R. (Roland); Barold, S. Serge; Sinnaeve, Alfons F. (Wiley Blackwell, 2015)
This brand new guide assists students, interns and residents in developing a functional understanding of the set-up, workings and interpretation of ECGs -Step-by-step graphics and short, bite-sized explanations -Covers all major cardiac abnormalities including hypertrophy, arrhythmias, conduction blocks, and pre-excitation syndromes -Begins with a section on physiology of the heart and the basic set up of ECG recording -Features top tips on what to look for, complete with illustrated examples -Supported by a companion website featuring additional practice tracings.